Answer:
x = 1
General Formulas and Concepts:
Pre-Algebra
Order of Operations: BPEMDAS
- Brackets
- Parenthesis
- Exponents
- Multiplication
- Division
- Addition
- Subtraction
Equality Properties
Explanation:
Step 1: Define Equation
3(4x - 5) - 4x + 1 = -6
Step 2: Solve for x
- Distribute 3: 12x - 15 - 4x + 1 = -6
- Combine like terms: 8x - 14 = -6
- Isolate x term: 8x = 8
- Isolate x: x = 1
Step 3: Check
Plug in x into the original equation to verify it's a solution.
- Substitute in x: 3(4(1) - 5) - 4(1) + 1 = -6
- Multiply: 3(4 - 5) - 4 + 1 = -6
- Subtract: 3(-1) - 4 + 1 = -6
- Multiply: -3 - 4 + 1 = -6
- Subtract: -7 + 1 = -6
- Add: -6 = -6
Here we see that -6 does indeed equal -6.
∴ x = 1 is the solution to the equation.